A Review and Current Status of Crime Prevention through Environmental Design (CPTED) - Cozens, Paul; Love, T. (2015)
This article reviews the current status of the concept of Crime Prevention through Environmental Design (CPTED). It provides an overview of its history and origins and defines how it is commonly understood and conceptualized. Globally, CPTED is an increasingly popular crime prevention strategy supported by governments all over Europe, North America, Australia, and New Zealand, as well as in Asia and South Africa. This review inspects some of the evidence associated with CPTED and provides a detailed overview of the main criticisms facing this field.